To drill or not to drill? An econometric analysis of US public opinion. (April 2016) - Mukherjee, Deep; Rahman, Mohammad Arshad
Abstract: Offshore drilling in the United States (US) has been the subject of public and political discourse due to multiple reasons which include economic impact, energy security, and environmental hazard. Consequently, several polls have been conducted over time to gauge public attitude towards offshore drilling. Nevertheless, the economic literature on this issue is sparse. This paper contributes to the literature and analyzes support for offshore drilling based on demographic, economic, social, belief, and shock (e.g. spill) factors. The data is taken from ten nationwide surveys conducted before, during and after the British Petroleum (BP) oil spill and analyzed within the framework of discrete choice model. The results from an ordinal probit model demonstrate that age, annual household income, affiliation to Republican Party, and residence in oil-rich states positively affect the probability of strong support and reduce the probability of strong opposition for offshore drilling. In contrast, the female gender, higher education, association to Democratic Party, and environmental concern affect opinion in opposite direction. Marginal effects show that belief about environmental consequences of drilling has the highest impact on opinion. Binary probit model also yields a similar result and suggests that BP oil disaster resulted in a transient decrease in support for offshore drilling. Abstract : Highlights: US public opinion on offshore drilling is analyzed based on ten national polls. Ordinal and binary probit models are utilized to identify the underlying factors that shape public opinion. Belief about environmental cost of drilling and educational attainment have the highest negative impact on opinion. Age, income, affiliation to Republican party and oil-rich states positively affect support for drilling. BP oil spill resulted in a transient decrease in support for offshore drilling.